MANAJEMEN SOSIALISASI ZAKAT PROFESI DALAM MENARIK SIMPATI WAJIB ZAKAT PADA BAZNAS KOTA MATARAM DAN BAZNAS NTB - Muslihun, Muslihun (JURNAL PENELITIAN KEISLAMAN, 2014)
This study discusses about: (1) the importance of socialization of professional zakat among the Muslim in Mataram, (2) effective strategy and tricks applied by Baznas City of Mataram and Baznas NTB in order to gain the interest of the muzakki (zakat submitters) in the city of Mataram. Based on the data resources, this research is field research, while observed from the nature of the data; this research is qualitative research with documentation study technique and interview in gathering the data. The gathered data are then analyzed and processed in order to generate conclusion. The findings of this research are: first, profession zakat is necessary to be socialized to Muslim people in Mataram because there are a lot of Muslims in Mataram who have less understanding upon the nature of professional zakat. Moreover, there are some of them who regard professional zakat is not obligatory alms upon them. Second, effective tips and tricks in order to obtain the interest of Muzakki candidate, i.e. (a) coming to the muzakki then give them some explanations about the nature of professional zakat, (b) circulating pamphlets and brochures that explain about professional zakat, (c) conducting dialogue program about professional zakat in TV and radio, (d) publishing all the activities of BAZNAS NTB and BAZNAS city of Mataram in particular through newspapers.